Cloud‐mediated self‐triggered synchronisation of a general linear multi‐agent system over a directed graph - Takumi Namba; Kiyotsugu Takaba (IET Cyber-Physical Systems)
Abstract The authors propose a self‐triggered synchronisation control method of a general high‐order linear time‐invariant multi‐agent system through a cloud repository. In the cloud‐mediated self‐triggered control, each agent asynchronously accesses the cloud repository to obtain past information about its neighbouring agents. Then, the agent predicts future behaviours of its neighbours as well as of its own and locally determines its next access time to the cloud repository. In the case of a general high‐order linear agent dynamics, each agent has to estimate exponential evolution of its trajectory characterised by eigenvalues of a system matrix, which is different from single/double integrator or first‐order linear agents. The authors’ proposed method deals with exponential behaviours of the agents by tightly evaluating the bounds on matrix exponentials. Based on these bounds, the authors design the self‐triggered controller through a cloud that achieves the bounded state synchronization of the closed‐loop system without exhibiting any Zeno behaviours. The effectiveness of the proposed method is demonstrated through the numerical simulation.